Islamic Education Curriculum:Between Classical Texts and the Challenges of the Modern Era - Azhar (Formad English Foundation NTB Jakarta, 2025)
This study explores the reconstruction of the Islamic education curriculum through a dialectical analysis of classical Islamic texts and modern educational challenges. The research aimed to investigate how classical Islamic educational values can be integrated with contemporary needs to form a holistic, responsive, and spiritually grounded curriculum. Utilizing a qualitative-descriptive approach through library research, the study drew from primary sources including classical works such as Ta‘līm al-Muta‘allim and Iḥyā’ ‘Ulūm al-Dīn, as well as secondary sources like modern literature, academic journals, and official curriculum documents. Data were collected using textual and documentation analysis, and analyzed thematically through stages of data reduction, display, and conclusion drawing. The findings revealed that classical Islamic curricula, though undocumented in modern formats, emphasized ethical-spiritual development (adab, akhlāq) and integrated revealed and rational sciences. In contrast, modern curricula face challenges such as secularization, fragmentation of knowledge, and the pressures of digital culture and global competencies. Recent reforms in institutions like UIN and Pondok Modern Gontor demonstrate promising models of integration. The study concludes that a reconstructed Islamic curriculum must revive the ideal of insān kāmil, blend tradition with innovation, and evaluate learners holistically in both cognitive and spiritual terms. These insights contribute to the ongoing discourse on Islamic curriculum reform in the 21st century.